Eficacia y eficiencia de Leader 11 en Andalucía. Aproximación a un índice-resultado en materia de turismo rural - Marquez Fernández, D.; Foronda Robles, C.; Galindo Pérez de Azpillaga, L.; García López, A. (Geographicalia, 2016)
The evaluation has turned into a strategic element of differentiation, into the measurement into that allows to demonstrate his own beneficiaries, that the application of the public or private resources, it is as suitable as possible. To evaluate is necessary a system of indicators, which answer to five big types of which we will centre on two: efficiency (the effort inverted in terms of plysical, human or financial resources and the obtained results) and effectiveness (the impacts or results of the program with regard to his aims). In this article we try to put of manifest as the evaluation of the measurement B.3 (tourist activities) it allows across the analysis of the efficiency (projects) and the effectiveness (investment) in LEADER 11, one approximation in the construction of a proved index.